Swede Hollow : A Novel - Larsmo, Ola, 1957- (Book collections on Project MUSE., 2019)
"Swedish novelist Ola Larsmo's historical novel Swede Hollow follows a group of Swedish immigrants at the turn of the 20th century and their experiences trying to forge a life for their families in Swede Hollow, a collection of shacks in a wooded ravine on the edge of the emerging industrial city of St. Paul"--